THE STUDENTS’ ACHIEVEMENT IN UNDERSTANDING PRAGMATICS MEANING OF WRITTEN UTTERANCES - Nunung Anugerawati Syam (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2012)
This research was attempted to find out the achievement of the sixth-semester students of English Department of Muhammadiyah University of Makassar especially Academic Year 2008 in understanding pragmatics meaning of the written utterances. This study employed a Descriptive research method. The sample of this study consisted of 40 students of the Sixth Semester Students of English Department Muhammadiyah University of Makassar which was selected by using simple random sampling. The instrument of the study was an objective test in the form of the checklist and identifying the locutionary, illocutionary, and perlocutionary acts of written utterances which consisted of 35 items. The test was administered to know the students’ achievement in understanding the pragmatic meaning of written utterances. The data obtained from the test was analyzed quantitatively. The mean score obtained from the test was 5, 87 for the locutionary act, 6, 12 for the illocutionary act, and 6, 09 for the perlocutionary act. The data showed that the students’ achievement in understanding the pragmatics meaning of written utterances especially the three layers of speech acts was fair. Key Words: Pragmatics, locutionary act, illocutionary act, perlocutionary act.